The effects of post‐frozen‐thawed embryo transfer pregnancy on early fetal development. Issue 3 (3rd January 2022) - Suga, Naoko; Oba, Mari S.; Kikuchi, Iwaho; Natori, Michiya; Hisamatsu, Kazuhiro; Hayashi, Satoshi
Abstract: Aim: Frozen‐thawed embryo transfer (FET) has gained popularity as an assistive reproductive technology despite its increased risk of large‐for‐gestational‐age offspring. This study aimed to analyze the effect of FET on fetal development, particularly the growth rate and estimated fetal weight (EFW) throughout pregnancy. Methods: This was a single‐center, retrospective study that examined 97 patients with FET conception and 477 patients with natural conception (NC) who underwent labor and delivery at our clinic between December 2015 and June 2019. Crown‐rump length (CRL) in the first trimester and EFW measurements in the second and third trimesters were obtained from transabdominal ultrasound records. Birthweight was adjusted for sex, parity, and gestational age. Regression coefficients of CRL, EFW, and birthweight were compared between the FET and NC groups to examine the growth rate. Multiple regression analysis was performed to determine the relationship between birth size and baseline characteristics. Results: The growth rate was higher in the first trimester in the FET group than in the NC group (difference: 0.19 mm/day, p  = 0.018). CRL, EFW, and adjusted birthweight were higher in the FET group than in the NC group throughout pregnancy. The factors associated with the development of larger offspring through FET than through NC were advanced maternal age, primiparity, cesarean section delivery, and high birthweight. Conclusions: Throughout pregnancy, FET resulted in a larger offspring than in NC, with accelerated growth observed only during the first trimester. Thus, FET highly affects early fetal development.